SPANISH ORIENTAL SCHOOL (Revista Inclusiones, 2021)
In Islamic history, it is traditionally considered that Spanish Orientalism is the first European study ofthe East, which was started in the colonial era between the 18th and 19th centuries. Orientalism wascreated by the Spanish world to study the countries of the East in the following directions: history,economics, geography, language, literature, anthropology, arts, religions, philosophy, archeology. Itspurpose is the subordination and control of the Eastern world in accordance with the objectives of theEuropean countries. It is divided into three main stages: colonial, post-colonial and the newOrientalism. The effects of Spanish Orientalism can be divided into positive – the dissemination ofIslamic heritage, the transfer of Islamic and Oriental knowledge in general to the West, the evolutionof the critical mental approach in the West, the coloring of the literary and artistic movement in theWest in an oriental tone, and the negative effects – the colonial, commercial, political, scientific,religious controls.